Analysis of the Technological Expenditures of Common WLAN Models - Kajackas, A.; Pavilanskas, L. (Elektronika ir Elektrotechnika, 2006)
Data presented of detailed technological WLAN analysis of efficiency of physical resources utilization and technological redundancy of IEEE 802.11 standard. Analysis performed by comparing two different modern technologies: the transmission by packets and transmission by channels. For the each WLAN transmitted packet formation headers of the different protocols are attached to the data block. Because of this the technological redundancy is increased. The various technological insertions determine increase of technological redundancy also. The contribution of each additional data blocks and time intervals is noted. Evolution of the possibilities of creation of adaptive WLAN protocols, witch may adapt to applied tasks conditions are pursued for analysis. Such protocols will utilize the physical radio channel effectively. One of predictable decisional way is the implementation of dynamic channel switching method. Ill. 7, bibl. 8 (in English; summaries in English, Russian and Lithuanian).